The neighbourhood relations in the urban environment between the urbanization and the countryside - Lokman REDAF (Social Sciences Journal, 1970)
This article treats the impact of the environmental change on urbanization types and urban change on theneighbourhood level,whereas the transition from rural to urban environment produces behaviours that oftencontradict the lifestyle of the city. Therefore a functional trouble will be resulted on the social and family relationsamong the inhabitants,and trends and behavioural patterns that are in contrast with urban values will appear,andthese will affect negatively the urban social system and the common lifestyle